Catalog of start and end times of lava fountaining episodes from 2 May to 14 June 2021 during the Fagradalsfjall eruption - Eibl, Eva P. S.; Gnauck, Undine; Hamzaliyev, Shaig; Hersir, Gylﬁ Páll; Gudnason, Egill Árni; Pétursson, Fridgeir (GFZ Data Services, 2022)
Abstract The Fagradalsfjall eruption from 19 March to 18 September 2021 featured lava fountaining episodes from 2 May to 14 June. These episodes were recorded as tremor pulses on our broadband seismic station NUPH (Nanometrics Trillium Compact 120s) at 5.5 km southeast of the active vent. We used the seismic data bandpass filtered between 1 and 4 Hz to mark the start and end of 7058 tremor pulses. The catalog hence comprises 14116 markers, that are statistically further evaluated in Eibl et al. (in review). From 2 May to 14 June, several changes in pulse duration and repose time were found and used to subdivide this time interval into 6 periods with characteristic pulse pattern. We find exponentially decreasing pulse durations, coexisting short and long pulses and stable pulse durations superimposed by gradually increasing or suddenly decreasing repose times. We discuss the findings in the context of an evolving shallow-conduit container, the crater geometries, partial collapses from the crater rim and the amount of accumulating outgassed magma in Eibl et al. (in review). This data publications releases the catalog of 14116 tremor pulses /lava fountaining episodes. Methods We installed a Trillium Compact 120 s seismometer (Nanometrics) as station NUPH (9F seismic network) at the southeast corner of Núpshlídarháls 5.5 km southeast of the eruptive site in Geldingadalir, Iceland. The instrument stood on a concrete base slab shielded from wind and rain using a bucket partly covered by rocks. The instrument was powered using batteries from 16 March, solar panels from 24 March and a wind generator at 10 m distance from 6 April 2021. Data were sampled at 200 Hz, they were stored on a Datacube and regularly downloaded. We used a compass to align the instrument to geographic north.